2013
DOI: 10.14207/ejsd.2013.v2n3p99
|View full text |Cite
|
Sign up to set email alerts
|

Cashew Apple Juice Anacardium Occidentale L Probiotic Fermented from Lactobacillus acidophilus

Abstract: The development of these probiotic beverages is important to diversify the market and to attend benefits to human health of large intestine. The aim of this study is using fruit juice from cashew apple as a substrate for the growth of Lactobacillus acidophilus. In order to create a new good probiotic beverages for human health and decrease environmental impurity from ripe cashew apples. The result shows that juice from ripe cashew apples after remove tannin and pasteurization at 90 0 C on 10 minutes and additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…However, there has been a trend for lower cholesterol, lactose free, dairy free, vegetarian, and vegan friendly options [3,6]. A number of studies have investigated the use of fruit juices as a medium for probiotic growth and viability [7][8][9][10][11][12][13][14][15][16][17][18][19][20]. These studies have demonstrated a potential for probiotics in a variety of different fruit juices such as orange, grape, pomegranate, peach, and apple.…”
Section: Introductionmentioning
confidence: 99%
“…However, there has been a trend for lower cholesterol, lactose free, dairy free, vegetarian, and vegan friendly options [3,6]. A number of studies have investigated the use of fruit juices as a medium for probiotic growth and viability [7][8][9][10][11][12][13][14][15][16][17][18][19][20]. These studies have demonstrated a potential for probiotics in a variety of different fruit juices such as orange, grape, pomegranate, peach, and apple.…”
Section: Introductionmentioning
confidence: 99%